Earthquakes - Radlauer, Ed (Chicago : Childrens Press, 1987)
Explores what causes earthquakes, where the tremendous power of a quake comes from, why they occur without warning, and whether it is possible to predict earthquakes.
Includes index.
Keywords: Earthquakes-Juvenile literature; Seismology-Juvenile literature; Earthquakes